KETERLIBATAN SISWA MELALUI METODE PEMBELAJARAN INTERAKTIF DAN TEKNIK PENILAIAN INOVATIF DI SEKOLAH DASAR: ANALISIS BIBLIOMETRIK - Faridah, Faridah; Oya, Abas; Suryaningsih, Sri; Fauzi, Azra (Pendikdas: Pendidikan Dasar, 2024)
This bibliometric analysis explores the impact of interactive learning methods and innovative assessment techniques on student engagement in primary education from 2019 to 2024. By analyzing a dataset of 1000 publications, the study highlights significant fluctuations in research outputs, particularly during the COVID-19 pandemic in 2022, which saw an increased focus on educational technology. Publication trends show a rise from 93 documents in 2019 to a peak of 253 documents in 2022, followed by a gradual decline to 150 documents in 2024, suggesting shifts in research priorities or the maturation of the field. The research identifies that video-based learning media and interactive multimedia are proven to be effective in enhancing student engagement and learning outcomes. Key findings indicate that these technologies significantly improve student motivation and learning outcomes while facilitating more innovative teaching practices among educators. The study also examines assessment techniques such as project-based assessment and self-assessment, which are shown to foster greater student engagement by encouraging active and collaborative learning. By synthesizing information across various studies, this research provides a comprehensive overview of the impact of interactive learning methods and assessment techniques on primary education and offers insights into their effectiveness and adaptability in diverse educational contexts.